2010
DOI: 10.1007/s11745-010-3471-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lecithin Source Affects Growth Potential and Gene Expression in Sparus aurata Larvae

Abstract: Soybean lecithin (SBL), used as a phospholipid source in larval fish diets, may compromise growth and survival in marine species, and affect gene expression, due to differences in fatty acid composition relative to marine lecithins (ML). The potential of SBL as a phospholipid source in gilthead seabream microdiets as compared to ML was evaluated. Two stocking densities were tested in order to exacerbate possible dietary effects: 5 and 20 larvae L(-1). Larvae reflected dietary fatty acid profiles: linoleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Relatively low survival was registered between 16 and 34 DAH, which may well relate to the stress of weaning (performed at an early life stage) combined with the fairly small tank volumes used in the rearing system. Still, the survivals observed are within the normal range for the species, despite higher values which have been reported when microdiets were offered at a later stage (43,55) . Relative growth rates may have reflected the same type of constraints, as higher values have been reported for sea-bream larvae fed caseinbased microencapsulated diets (56) .…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Relatively low survival was registered between 16 and 34 DAH, which may well relate to the stress of weaning (performed at an early life stage) combined with the fairly small tank volumes used in the rearing system. Still, the survivals observed are within the normal range for the species, despite higher values which have been reported when microdiets were offered at a later stage (43,55) . Relative growth rates may have reflected the same type of constraints, as higher values have been reported for sea-bream larvae fed caseinbased microencapsulated diets (56) .…”
Section: Discussionmentioning
confidence: 45%
“…Whole-body cortisol was determined in pooled larvae samples of about 150–300 mg per tank (wet weight), according to methodology which has been described previously ( 43 ) , and using a commercial cortisol ELISA kit (Neogen Corporation).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid classes (mg g −1 extracted lipid) of fillet of S. hasta juvenile fed experimental diets differing in their content in soybean lecithin (SBL) (mean ± SEM, n = 3). significantly increased with increasing dietary SBL levels, as it has also been reported in other fish species fed diets supplemented with SBL (Benedito-Palos et al 2008;Alves Martins et al 2010;Sotoudeh et al 2011;Azarm et al 2013;Saleh et al 2015;Salini et al 2016). Fish oil is the main source of the LC-PUFA, including arachidonic (20:4n-6, ARA), eicosapentaenoic (20:5n-3, EPA) and docosahexaenoic (22:6n-3, DHA) (Glencross 2009; Turchini et al 2009 Salini et al 2016).…”
Section: Discussionmentioning
confidence: 64%
“…2003b) and gilthead seabream (Seiliez et al. 2006; Martins et al. 2010) fed on tailored designed microdiets have shown that the level and source of phospholipids differing in its fatty acid composition affect the body composition in lipid classes and growth potential.…”
Section: Feed Formulationmentioning
confidence: 99%